Characterizing relationships of DTI, fMRI, and motor recovery in stroke rehabilitation utilizing brain-computer interface technology - Song, Jie; Young, Brittany M.; Nigogosyan, Zack; Walton, Leo M.; Nair, Veena A.; Grogan, Scott W.; Tyler, Mitchell E.; Farrar-Edwards, Dorothy; Caldera, Kristin E.; Sattin, Justin A.; Williams, Justin C.; Prabhakaran, Vivek (Frontiers in Neuroengineering, 2014)
The relationship of the structural integrity of white matter tracts and cortical activity to motor functional outcomes in stroke patients is of particular interest in understanding mechanisms of brain structural and functional changes while recovering from stroke. This study aims to probe these underlying mechanisms using diffusion tensor imaging (DTI) and fMRI measures. We examined the structural integrity of the PLIC using DTI and corticomotor activity using motor-task fMRI in stroke patients who completed up to 15 sessions of rehabilitation therapy using Brain-Computer Interface (BCI) technology. We hypothesized that 1) the structural integrity of the posterior limb of the internal capsule (PLIC) and corticomotor activity are affected by stroke; 2) changes in structural integrity and corticomotor activity following BCI intervention are related to motor recovery; 3) there is a potential relationship between structural integrity and corticomotor activity. We found that 1) the ipsilesional PLIC showed significantly decreased fractional anisotropy (FA) values when compared to the contralesional PLIC; 2) lower PLIC-FA values were significantly associated with worse motor outcomes (i.e., positively correlated); 3) lower ipsilesional PLIC-FA values were significantly associated with greater ipsilesional corticomotor activity during impaired-finger-tapping-task fMRI (i.e., negatively correlated), with an overall bilateral pattern of corticomotor activity observed; and 4) baseline FA values predicted motor recovery assessed after BCI intervention. These findings suggest that greater vs. lesser microstructural integrity of the ipsilesional PLIC may contribute towards better vs. poor motor recovery respectively in the stroke-affected limb and demand lesser vs. greater cortical activity respectively from the ipsilesional motor cortex. PLIC-FA is a promising biomarker in tracking and predicting motor functional recovery in stroke patients receiving BCI intervention.